2007
DOI: 10.1176/ps.2007.58.7.962
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mental Health Care Services by Canadians With Co-occurring Substance Dependence and Mental Disorders

Abstract: The differential use of services, satisfaction, and unmet need across diagnostic status allowed for speculation on differing levels of disability and stigma in the help-seeking process for different types of disorders. The strong association between co-occurring disorders and unmet need for care, including a large proportion of respondents who stated they preferred to self-manage their symptoms, is particularly troubling and deserves future research attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 54 publications
10
62
0
1
Order By: Relevance
“…Efforts to integrate primary health care and specialty mental health and substance abuse services should also account for this subpopulation, as help seeking is by no means restricted to the specialist sector. 39,45 The appropriate treatment response for co-occurring disorders depends on the person and the severity of the disorders. 46 In addition to the exclusion of several mental disorders, noted above, other limitations of the present research should be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to integrate primary health care and specialty mental health and substance abuse services should also account for this subpopulation, as help seeking is by no means restricted to the specialist sector. 39,45 The appropriate treatment response for co-occurring disorders depends on the person and the severity of the disorders. 46 In addition to the exclusion of several mental disorders, noted above, other limitations of the present research should be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Males are more likely than females to have substance dependence, mainly using alcohol and marijuana. 11,14 Previous studies 48,49 also found that co-occurring disorders were more prevalent among young people. It is logical that substance dependence would occur during young adulthood, considering that adolescence is usually the period of initiation to drugs.…”
Section: 40mentioning
confidence: 95%
“…11,13 Younger people are more likely to abuse substances, whether they have co-occurring disorders or not. 14,15 People with an SUD are less likely to have a post-secondary education 16 or high household incomes. 15 However, people whose sole affliction is substance dependence have lower psychological distress than those affected by co-occurring disorders.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This group often shows no desire to receive treatment, and motivational therapy and harm reduction initiatives must therefore become essential elements of a rehabilitation plan. In 2002, for example, the ratio of Canadians seeking the advice of a family physician, psychiatrist or psychologist within a 12-month period were respectively 6.2, 1.8 and 2.3 percent among individuals with substance dependence, 31.6, 14.1 and 10.0 percent among those with mental disorders, and 34.6, 16.1 and 11.0 percent among those with co-occurring disorders [21]. These groupsand especially persons with only a substance abuse problemtherefore use services well below the optimal level that might address their actual needs [22,23].…”
Section: Introductionmentioning
confidence: 99%